On the synthesis of SiC single crystals - Inomata, Yoshizō; Tanaka, Hirokichi.; Air Force Cambridge Research Laboratories (U.S.) (Air Force Cambridge Research Laboratories, Air Force Systems Command, United States Air Force, 1972)
A method is proposed to synthesize SiC single crystals free of carbon particle inclusions. An empty graphite crucible is connected with the crucible containing silicon melt by means of a graphite pipe. The former crucible is heated to approximately 2,500C, as in the ordinary sublimation process, while the temperature of the latter is lowered. Crystal growth is accomplished in the empty crucible. The experiments conducted are preliminary. Problems such as damages to the crucible containing silicon melt, prevention of silicon leak, and control of the amount of silicon supply to the growth cavity are examined. The structure of the furnace necessary for the implementation of the method is discussed.
Translation supported by the Air Force Cambridge Research Laboratories, Air Force Systems Command, United States Air Force (L.G. Hanscom Field, Mass.), and translated by the Oriental Science Research Library of Emmanuel College, Boston, Massachusetts, under Contract F19628-71-C-0121
Translated from Ceramic Society of Japan Journal (Yogyo Kyokai-Shi). v. 79, n. 10, pp. 392-395, 1971
AFCRL Research Library.
AD0752227 (from http://www.dtic.mil).
"5 September 1972."
Keywords: Silicon carbide. / fast / http://id.worldcat.org/fast/1118657; Crystals. / fast / http://id.worldcat.org/fast/884667; Crystal growth. / fast / http://id.worldcat.org/fast/884619; Crystals. / http://id.loc.gov/authorities/subjects/sh85034503; Crystal growth. / http://id.loc.gov/authorities/subjects/sh85034507; Silicon carbide. / http://id.loc.gov/authorities/subjects/sh85122519